L’iconicité des hiéroglyphes égyptiens: La question de la mutilation - Thuault, Simon (Zeitschrift für ägyptische Sprache und Altertumskunde, 2020)
Although mutilation is a well-known process of Egyptian hieroglyphic writing system, its involvement in signs’ figurativity and iconicity has benefited of less attention. Yet, the mutilation practice could have deep consequences for the grammatological nature of hieroglyphs, implying alterations in our analysis of the whole Egyptian scriptural functioning. Thus, this paper aims to shed light, through examples of mutilated signs, on the iconic essence of the affected hieroglyphs: does the alteration of a sign impact its iconicity and, due to this, its raison d’être in a clause or a lexeme? Since there are kinds of mutilation, do they result in various implications in our linguistic analysis of the sign? Moreover, what metonymical relations can we observe in this process? These linguistic and psychological issues will allow to complete our understanding of the mutilation practice and, consequently, of the essence of hieroglyphic signs.